Гостинність як риса національного характеру українців - Русавська, В.А. (Культура народов Причерноморья, 2014)
В статті розглядаються особливості характеру українців в контексті гостинності,
специфіка якої була зумовлена складовими його ментальності, серед яких головними є специфіка
селянського світосприйняття, соціальна психологія селян, правова свідомість, релігійні погляди. В статье рассматриваются особенности характера украинцев в контексте
гостеприимства, специфика которого была обусловлена составляющими его ментальности, среди
которых главными являются специфика крестьянского мировосприятия, социальная психология
крестьян, правовое сознание, религиозные взгляды. In the article it is considered the peculiarities of the Ukrainians nature within a context of hospitality.
Its specificity was determined by elements of mentality among which the main one is a specificity of rural world
perception, social psychology of countrymen, their legal consciousness and religious commitment.
The hospitality of Ukrainian people has been establishing during a long phase of history and had an effect on
formation of national character.
The national character in its turn reflects deep structures of psychology both personal and national which
determine the way of world perception, practical attitude to society, themselves and nature.
That’s why the main character features of the Ukrainians during the whole history have been affected by natural
and socio-political factors, by Ukrainian material culture the background of which is a household activity. The
hospitality is presented as a result of socio-cultural processes during a long phase of history, a reflection of
national character, moral and ethical values, lifestyle and type of behavior.
Whereas the hospitality as the embodiment of personal forms of social being and world imaging is one of the
structural elements of national mentality which is a complex of psychical, intellectual, religious, sensuous and
other peculiarities of thinking which are detected in culture, language and behavior, then the peculiarities of
Ukrainian character are represented in it.